Patterns of Cultural Transplantation in the English Translation of Goenawan Mohamad’s Poem “Pastoral” - Wiraswastiningrum, Ni Wayan Swardhani; Junining, Esti; Yulianto, Wawan Eko (Universitas Brawijaya, 2026)
This study examines the translation of cultural terms in the poem “Pastoral,” focusing on strategies used to achieve clarity and comprehension in the target language (TL). The findings show that cultural transplantation is primarily realized through adaptation as the dominant strategy, followed by addition and reduction. These strategies reflect the translator’s effort to balance fidelity to the source text (ST) with accessibility for target readers. Although some cultural nuances may be reduced, these procedures enhance readability and support clearer understanding of meaning. Cultural transplantation thus serves as a key approach in bridging cultural differences, enabling the themes and emotional depth of the original poem to be conveyed effectively in the target text (TT). The study also highlights the role of translation in facilitating coherent intercultural communication. Future research is recommended to apply comparative analyses across literary texts to identify patterns in translating cultural terms and deepen insights into the relationship between language, culture, and translation.